The Functioning of Romantic Love Myths as an Interpretive Framework for Young Girls' Experiences of Romantic Relationships: An Interpretative Phenomenological Analysis - Kacprzak-Wachniew, Kamila; Spychalska-Stasiak, Justyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
In this article, we explore young girls' love experiences and their conceptions of love in the context of changing intimacy and diverse relationship models. In order to gain insight into how adolescent girls understand their experiences of affection, we conducted a study using Interpretive Phenomenological Analysis. Following the IPA assumptions, the sample selection was purposeful. Features were established on the basis of which a homogeneous group was identified, whose experiences will not be differentiated due to: the number and nature of experiences (no more than three or a maximum of four heterosexual emotional relationships), attitudes to religion (moderate) and family type (full). The research involved in-depth interviews with six adolescent girls who had experiences of affectionate relationships. The interview transcriptions constituted the raw empirical material analysed according to IPA guidelines (Smith et al., 2009). The analyses aimed to annotate the transcriptions, identify emerging themes and collate them in search of common super‐ordinate themes. Four themes emerged from the analysis that were common across the study group. One of these, described in detail, concerned the belief in myths associated with romantic love and its impact on young girls' perceptions of relationships and interpretations of emotional experiences. The t super‐ordinate theme emerging from the narratives of the female respondents are related to the culturally sustained belief in the possibility of finding the 'perfect partner' and the romantically enmeshed belief in 'true love', whose strength is able to overcome all difficulties. Our analyses revealed that romanticising relationships provides a framework for interpreting one's own experiences, but also shapes these experiences (motivating certain behaviours, e.g. to 'fight for an emotional relationship'. Belief in romantic myths, e.g. the idealisation of the relationship and the partner, can cause difficulties in ending relationships, detrimental to their young person's mental health.